Creating cross-platform C# applications with Uno : build apps with C# and XAML that run on Windows, macOS, iOS, Android, and WebAssembly /: build apps with C# and XAML that run on Windows, macOS, iOS, Android, and WebAssembly. (2021) - (Application developer), Lacey, Matt; Wagner, Marcel
No abstract available